Ecofriendly production of silver nanoparticles from the seeds of Carica papaya and its larvicidal and antibacterial efficacy against some selected bacterial pathogens. Issue 1 (March 2020) - Aina, AD; Owolo, O; Adeoye-Isijola, M; Olukanni, O D; Lateef, A; Egbe, T; Aina, FO; Asafa, TB; Abbas, SH
Abstract: Carica papaya seed extract (CPE) was used in the synthesis of silver nanoparticles (AgNPs) in this study. For the characterization of biosynthesized particles, UV-vis spectroscopy, FTIR, FESEM and EDX were used. Antimicrobial and larvicidal efficacies of the synthesized AgNPs were assessed in the fight against certain pathogens and the Aedes aegypti 4th instar larvae. The absorption spectrum of AgNPs peaked at 433 nm with a broad peak of 3000 to 3800 cm −1 for different functional groups as presented in the FTIR analysis. A FESEM evaluation revealed a number of spherical particle structures with an average of 20-69 nm. With zones of inhibition between 10-24 mm, the AgNPs synthesized inhibited selected microorganisms. After 12 h of exposure, the nanoparticles had LC50 and LC90 lethal concentration on the Aedes aegypti larva at 14.56 and 33.89 μg/ml respectively. This study demonstrates possibility of using Carica papaya seeds in AgNPs synthesis.